A rare occurrence of reversal in the common megrim Lepidorhombus whiffiagonis (Pleuronectiformes: Scophthalmidae) in the northern North Sea. Issue 3 (14th August 2013) - MacDonald, P.
<x xml:space="preserve">Abstract</x> An adult (231 mm standard length, LS; 371 mm total length, LT), dextral (right‐sided) common megrim Lepidorhombus whiffiagonis is reported from the northern North Sea. This is the first recorded occurrence of reversal in this species. Other than its reversed asymmetry, the specimen had morphological and meristic characteristics similar to those of non‐reversed individuals of the same species.